Inhibition of N2 Fixation by N Fertilization of Common Bean (Phaseolus vulgaris L.) Plants Grown on Fields of Farmers in the Eastern Cape of South Africa, Measured Using 15N Natural Abundance and Tissue Ureide Analysis - Habinshuti, Simon J.; Maseko, Sipho T.; Dakora, Felix D. (Frontiers in Agronomy, 2021)
Inhibition of N2 fixation in N-fertilized common bean (Phaseolus vulgaris L.) plants growing on the fields of farmers in the Eastern Cape of South Africa was measured using 15N natural abundance and tissue ureide analysis. The N-fertilized bean plants revealed greater soil N uptake, higher concentrations of nitrate in organs, low tissue ureide levels, and much lower percent relative ureide-N abundance when compared with unfertilized plants. In contrast, the unfertilized plants showed greater nodule fresh weight, higher N derived from fixation (e.g., 84.6, 90.4, and 97.1% at Lujecweni fields 2, 3, and 4, respectively), increased amount of N-fixed (e.g., 163.3, 161.3, and 140.3 kg ha−1 at Lujecweni fields 2, 3, and 4, respectively), greater ureide concentration in stems and petioles, higher % relative ureide-N abundance, and low soil N uptake. We also found that the percent N derived from fixation (%Ndfa) was very high for some bean plants receiving a double dose of N fertilizer [e.g., Lujecweni field 1 (51.8%) and Tikitiki field 1 (53.3%], and quite high for others receiving a single dose of N fertilizer [e.g., Tikitiki field 2 (50.1%), Mfabantu fields 1 and 2 (45.5 and 79.9%, respectively), and St. Luthberts field 1 (58.9%)]. Though not assessed in this study, it is likely that the rhizobia that effectively nodulated the N-fertilized bean plants and fixed considerable amounts of symbiotic N had constitutive and/or inducible nitrate reductase genes for reducing nitrate in nodules and bacteroids, hence their ability to form root nodules and derived high %Ndfa in bean with added N. While single- and double-dose N fertilizer applications increased plant growth and grain yield compared to unfertilized bean plants, the single-dose N fertilizer application produced much greater grain yield than the double dose. This indicates that farmers should stop using a double dose of N fertilizers on bean production, as it decreases yields and can potentially pollute the environment. This study has however shown that government supply of free N fertilizers to resource-poor farmers in South Africa increased bean yields for food/nutritional security.